2013
DOI: 10.1149/2.001303eel
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Kinetics Studies in All-Vanadium Redox Flow Batteries

Abstract: We report results of polarization measurements resolved for the negative and positive electrodes of vanadium redox batteries (VRBs) using a dynamic hydrogen electrode in an operating battery cell. Electrochemical experiments with symmetric electrolyte feeds were also performed. Greater kinetic polarization is observed at the negative (V 3/2+) electrode compared to the positive electrode (V 5/4+), in contrast with previously reported ex situ measurements. For the positive electrode, the polarization in the low-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
103
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(110 citation statements)
references
References 12 publications
7
103
0
Order By: Relevance
“…The polarization of the V(ii)/V(iii) couple exceeds that of the V(iv)/V(v) couple for this particular set of materials and activation procedures. This observation is consistent with the recent findings of Aaron et al(4).…”
supporting
confidence: 94%
“…The polarization of the V(ii)/V(iii) couple exceeds that of the V(iv)/V(v) couple for this particular set of materials and activation procedures. This observation is consistent with the recent findings of Aaron et al(4).…”
supporting
confidence: 94%
“…Most studies in the past, however, report overall battery parameters (cell resistance or efficiency) and hence conclude with rather general statements. More detailed investigations using reference electrodes or non‐symmetric felt combinations at the positive and negative electrodes have shown that the negative electrode is more problematic with respect to the kinetic overpotential. In fact, recent systematic studies of the electrochemical pretreatment of various carbons (glassy carbon, carbon fibers, graphite) have even revealed opposing effects for both redox couples when subjected to anodic or cathodic pre‐treatment .…”
Section: Introductionmentioning
confidence: 99%
“…Unlike the aforementioned four-tank and two-tank EFC approaches, these experiments were performed using only a single tank. This approach is analogous to the symmetric cell experiments of flow batteries; 18,19 instead of storing the positively and negatively charged slurries for subsequent discharge, the outflows from both half cells are simply remixed to a uniform uncharged state in the single reservoir. Doing so allows for consistent uncharged conditions at the inlets of the EFC half-cells.…”
Section: Methodsmentioning
confidence: 99%